Computed tomographic airway morphology after targeted lung denervation treatment in COPD - Hartman, Jorine E.; Herth, Felix; Shah, Pallav; Pison, Christophe; Valipour, Arschang; Slebos, Dirk-Jan (Respiratory medicine, 2023)
This post-hoc analysis of the AIRFLOW-2 trial investigated the changes in airway CT-parameters after targeted lung denervation (TLD) and whether these changes are associated with treatment response. In the treatment group (n = 32), an improvement in air trapping was significantly associated with an improvement in residual volume (RV). Furthermore, improvements in Pi10 and airway lumen were significantly associated with an improvement in both RV and FEV1. Our results could suggest that when improving airway characteristics like decreasing airway wall thickness and increasing the airway lumen, this leads to less air trapping and an improvement in clinical outcomes.
Online verfügbar 26. November 2022, Artikelversion 29. November 2022
Gesehen am 15.06.2023